2021
DOI: 10.1016/j.annonc.2021.05.142
|View full text |Cite
|
Sign up to set email alerts
|

P-87 Real-world data of nivolumab in advanced hepatocellular carcinoma: A multi-centric and retrospective study

Abstract: There was no heterogeneity between studies (I 2 ¼ 0%; p ¼ 0.6). Conclusions:The response rate to neoadjuvant chemotherapy is very low in MSI-H tumors. MSI status should be considered while deciding for neoadjuvant therapy in locally advanced gastric or gastroesophageal junction cancer. In the MSI-H group, the response rate may increase with the use of immunotherapies in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Overall, efficacy was approximately half of that observed in Checkmate 040. Results from this study are in agreement with latest evidence indicating that the survival of patients with aHCC treated with nivolumab is correlated to the Child-Pugh liver function score at baseline[ 95 ], as reported in aforementioned studies as well[ 92 - 94 ]. Equally, the finding that unselected Child-Pugh B and above patients exhibit an unsatisfactory response to and survival with nivolumab has been echoed in another retrospective study of 203 HCC patients; (ORR 3% vs 16% in Child–Pugh class B/A, P = 0.01; mOS 11.3 vs 42.9 wk in Child–Pugh class B/A, adjusted HR, 2.10, P < 0.001)[ 96 ].…”
Section: Real-world Data For Immunotherapy In Hccsupporting
confidence: 92%
“…Overall, efficacy was approximately half of that observed in Checkmate 040. Results from this study are in agreement with latest evidence indicating that the survival of patients with aHCC treated with nivolumab is correlated to the Child-Pugh liver function score at baseline[ 95 ], as reported in aforementioned studies as well[ 92 - 94 ]. Equally, the finding that unselected Child-Pugh B and above patients exhibit an unsatisfactory response to and survival with nivolumab has been echoed in another retrospective study of 203 HCC patients; (ORR 3% vs 16% in Child–Pugh class B/A, P = 0.01; mOS 11.3 vs 42.9 wk in Child–Pugh class B/A, adjusted HR, 2.10, P < 0.001)[ 96 ].…”
Section: Real-world Data For Immunotherapy In Hccsupporting
confidence: 92%
“…The most common 2L treatments following sorafenib were nivolumab (37.5%), regorafenib (23.6%), and capecitabine (6.9%); other real-world studies have demonstrated the effectiveness of these therapies when used as 2L treatments following sorafenib. In another real-world study, survival of 23 patients with advanced HCC who received nivolumab after 1L sorafenib treatment was shown to relate with CP score at the start of treatment; CP Class A at initiation of nivolumab was associated with superior OS (p = 0.014) [ 33 ]. Experience of treatment sequencing from sorafenib to regorafenib in the real-world setting has also been reported with an increase in OS and tolerable safety profile, similar to that observed in clinical trials [ 34–36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another major challenge in immunotherapy for HCC is the lack of markers to predict the effect of treatment. The latest report in the ESMO 2021 Annual Meeting shows that the survival of patients with advanced HCC treated with nivolumab was related to the Child-Pugh (C-P) liver function score at baseline (136). However, other methods of immunotherapy are mostly still in the early clinical stage, and there are no good indicators for predicting the therapeutic effect.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%